2022
DOI: 10.3171/2021.7.spine21413
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the difference between lumbar lordosis in the supine and standing positions on the clinical outcomes of decompression surgery for lumbar spinal stenosis

Abstract: OBJECTIVE The authors sought to evaluate the relationship between the difference in lumbar lordosis (DiLL) in the preoperative supine and standing positions and spinal sagittal alignment in patients with lumbar spinal stenosis (LSS) and to determine whether this difference affects the clinical outcome of laminectomy. METHODS Sixty patients who underwent single-level unilateral laminectomy for bilateral decompression of LSS were evaluated. Spinopelvic parameters in the supine and standing positions were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…[ 5 , 18 ] More recently, preoperative difference in lumbar lordosis between standing and supine positions (DiLL) was proposed as a predictive factor for postoperative lumbar alignment changes after lumbar surgery for lumbar degenerative disease. [ 3 , 13 , 15 ] From our experience, it is suggested that postural differences in LKA are useful for evaluating the stability of thoracolumbar fractures after fusion surgery and predicting postoperative loss of correction.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 , 18 ] More recently, preoperative difference in lumbar lordosis between standing and supine positions (DiLL) was proposed as a predictive factor for postoperative lumbar alignment changes after lumbar surgery for lumbar degenerative disease. [ 3 , 13 , 15 ] From our experience, it is suggested that postural differences in LKA are useful for evaluating the stability of thoracolumbar fractures after fusion surgery and predicting postoperative loss of correction.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple regression analysis was performed to exclude the influence of age, sex, BMI, scoliosis, and number of fused segments and a significant correlation was found between DiLL and each clinical score. As DiLL and PI-LL were found to be significantly correlated 34 , the two values could not be used in the multiple regression analysis to avoid multicollinearity. However, this study revealed that the difference in outcomes between patients with DiLL (+) and those with DiLL (−) was more evident in patients with PI-LL mismatches.…”
Section: Discussionmentioning
confidence: 99%